Implementasi Augmented Reality untuk Aplikasi Media Promosi Produk Mebel Jepara Berbasis Android - Mukti, Farhan Widyana; Asriningtias, Yuli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Jepara Regency is known as one of the centres of furniture production in Indonesia thanks to its distinctive wooden crafts. Many furniture industries in this area have adopted the strategy of marketing through catalogues as a promotional medium, but with the rapid popularity of smartphone use, the use of social media as a marketing tool for furniture products has also increased. This has resulted in marketing through catalogues of furniture products via social media becoming commonplace and less effective. The ineffectiveness of catalogue media is because it has limitations that can only convey information in the form of images, while the selection of furniture products requires design considerations according to customer preferences. With problems arising related to the effectiveness of furniture marketing strategies, innovation is needed in product visualisation. The proposed solution is to use Augmented Reality (AR) technology on promotional media. Augmented Reality (AR) is a technology that combines digital information with the user's environment in real-time. In this research, an Android-based furniture promotion application is developed with the Extreme Programming method that utilizes AR technology to visualise furniture product designs in 3D and is designed using the Unified Modelling Language (UML). It is expected that this application can increase interest and facilitate customers in finding furniture products, as well as support the furniture industry in promoting its products.